The Protection of Arwana Kelesak As A Native Species of Bangka Belitung - Kusuma, Winanda; Permatasari, Bunga (Jambe Law Journal, 2022)
The protection of wildlife should be a concern of international law that is regulated in a legal framework agreed upon by the state by respecting sovereignty in implementing international law. Yet the implementation of sovereignty is a challenge for wildlife protection. In Bangka Belitung region in Indonesia live native species, one of which is the Arowana Kelesak. This species of fish in the fresh waters of Bangka Belitung without human intervention and, yet is not a native species. The priority of local regulations on the Arowana Kelesak species is still negligible. Therefore, the efforts to make this fish endangered status have to begin from the area where they live as long as the regulations are concerned. On the other hand, the application of Indonesian laws is not prioritized. The lack of valid scientific data is another challenge. This article aims to ensure that regional regulation of Arwana Kelesak is a necessity because CITES has listed this species as endangered. International legal regulations must be the basis for protecting species that Indonesia has ratified so that the seriousness of the regulations must be clear. On top of that, scientific information from the region regarding the location of the habitat is difficult to find and cannot be used as evidence to claim the threat of extinction. Whilst, illegal tin mining activities in this area pose an additional challenge to the protection of Arwana Kelesak. It is evidence that the mining pit has damaged freshwater ecosystems, especially such native species as the Arwana Kelesak. This article argues that international law through CITES and IUCN has to be taken into account by Bangka Belitung government. Similarly, local regulations and the attention of the central government as the official management authority of CITES need to be ensured to protect the Arwana Kelesak